The Effectiveness of Educational Videos in Improving Vocabulary Mastery at SMP Negeri 16 Palu - Rahmawati Rahmawati; Abd. Kamaruddin; Maf’ulah Maf’ulah; Mochtar Marhum (MASI Mandiri Edukasi, 2026)
Vocabulary mastery is a fundamental component of English as a Foreign Language (EFL) learning; however, preliminary observations at SMP Negeri 16 Palu revealed that many eighth-grade students still have limited vocabulary. Students experienced difficulties in understanding word meanings, identifying word classes, and using vocabulary appropriately in simple sentences, which negatively affected their participation, confidence, and comprehension in English learning. Therefore, this study aimed to find out the effectiveness of educational videos in improving students’ vocabulary mastery. This study employed a quantitative, quasi-experimental research design. The population consisted of 129 eighth-grade students of SMP Negeri 16 Palu in the 2024/2025 academic year. The samples were class VIII C as the experimental group and class VIII E as the control group. The research instruments were vocabulary tests administered as pre- and post-tests, focusing on nouns, verbs, and adjectives. The collected data were analysed using a normality test, a homogeneity test, and an independent-samples t-test in SPSS version 24. The findings indicated that the experimental group achieved a higher mean post-test score (70.27) compared to the control group (58.93). The result of the independent samples t-test showed a significance value of 0.001, which was lower than 0.05, indicating a statistically significant difference between the two groups. These results demonstrate that the use of educational videos, particularly animated videos, effectively improves students’ vocabulary mastery.